2014
DOI: 10.1590/1806-9282.60.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sexual function in middle-aged women

Abstract: Objective: To investigate the relationship between physical activity level and sexual function in middle-aged women. Methods: A cross-sectional study with a sample of 370 middle-aged women (40-65 years old), treated at public health care facilities in a Brazilian city. A questionnaire was used containing enquiries on sociodemographic, clinical and behavioral characteristics: the International Physical Activity Questionnaire (IPAQ), short form, and the Female Sexual Function Index (FSFI). Results:The average ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 28 publications
4
32
0
6
Order By: Relevance
“…Increased blood flow and improved self-confidence are factors affected positively by exercise in sexual desire (5,24). With regards to the simultaneous use of antidepressants and aerobic exercise, the findings in our study were consistent to the findings of the studies conducted by Lorenz and Meston (14) and Cabral et al (12).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased blood flow and improved self-confidence are factors affected positively by exercise in sexual desire (5,24). With regards to the simultaneous use of antidepressants and aerobic exercise, the findings in our study were consistent to the findings of the studies conducted by Lorenz and Meston (14) and Cabral et al (12).…”
Section: Discussionsupporting
confidence: 92%
“…In women, physical activities decrease with age and women are less active than men and tend to spend their leisure time in less strenuous activities. In addition, evidence showed that physical exercise alters menopausal symptoms, sleep cycle, moods, stress, depression and musculoskeletal disorders in women (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women whose average age of 49.8 years, Cabral et al found that physically active women obtained higher score in all FSFI domains (desire, arousal, lubrication, orgasm, satisfaction and pain) and total FSFI score (20.9), indicating better sexual function than their moderately active (18.8) and sedentary (15.6) counterparts. 27 The next important finding of this study is respondents who menstruate at the age <15 years tend to show quality of sexual function better than those who menstruate at age ≥15 years. Seemingly, this phenomenon related to the main estrogenic hormone conditions, 17-β-estradiol.…”
Section: Discussionmentioning
confidence: 66%
“…There is a strong association between physical activity and sexual function, as well as physical inactivity and sexual dysfunction (78.9%) in inactive women compared to active ones (57.6%) (Cabral et al, 2014). Corroborating these findings, (Margolis, 2006) and (Santos, 2010), has also considered that sexual activity is an important physical activity and can reduce sexual dysfunction, providing biopsychosocial wellness able to boost immunity.…”
Section: Discussionmentioning
confidence: 94%